Literature Review: Factors Caused an Increase the Number of Early Marriage during the Covid-19 Pandemic - Ismiati Ismiati; Fuji Khairani; Teguh Achmalona (Journal of Ners and Midwifery, 2022)
Early marriage is an issue that is quite hotly discussed at this time, especially during the COVID-19 pandemic. The reason is, during the COVID-19 pandemic, there was an increase in the number of early marriages which became a serious threat to women's health, dignity and autonomy. This study aimed to determine the factors that cause an increase in early marriage during the COVID-19 pandemic. The method a literature review was conducted using the Google Scholar, Pubmed, and Science Direct databases to search for national and international journals researching early phenomena during the COVID-19 pandemic. The results of a review of 6 journals showed that the factors that cause an increase in early marriage during the pandemic are caused by several factors, namely economic problems, free sex, lack of knowledge in children, low awareness and knowledge of parents about the impacts and risks arising from child marriage, both physically and mentally. , mental, social and psychological, cultural and because they believe that marriage is an escape from schoolwork, homework, and the stress and boredom of studying and staying at home during a pandemic.Conclusion: From the results of a journal review, it can be concluded that the COVID-19 pandemic has impacted many aspects of life and continues to be felt throughout the world. Including the increase in marriage during the COVID-19 pandemic. To prevent an increase in child marriage, namely the existence of social protection interventions related to social, economic and educational empowerment of adolescents, especially poor youth during the pandemic. and joint efforts are needed involving parents, victims, community leaders, faith-based organizations, governments, international agencies and stakeholders related to preventing early marriage, especially during a pandemic.